Zoneamento de áreas suscetíveis a deslizamentos: centro urbano de Parauapebas, Pará - COIADO, Luíza Lara (2024)
The action of environment factors associated with the accelerated growth of cities without strategic urban planning has presented problems in the prevention of disasters resulting from mass movements and floods. This is the case of the municipality of Parauapebas, in the state of Pará, which, due to natural characteristics and the occupation of urban land, has shown itself to be vulnerable to this phenomenon. In this sense, the present work aimed to evaluate the susceptibility to mass movements in the city of Parauapebas, PA, in a GIS environment (Geographic Information Systems) using Fuzzy Logic and the Analytical Hierarchical Process - AHP. For this, slope vectors, geomorphology, lithology, pedology, risk sectorization, slip points and slope cuts were taken into account. A weight was assigned to each of these characteristics and through map algebra, associated with fuzzy logic, it was possible to spatially determine the susceptibility of mass movement for the region. As a result, the Susceptibility to Mass Movement map was generated for the urban center of the municipality of Parauapebas by the fuzzy gamma inference. This method presented satisfactory results as an accessible tool for urban planning and landslide management, in order to avoid loss of life and materials.